2017
DOI: 10.1002/adma.201606741
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Doping Effect and Unusually Large Angle van Hove Singularity Evolution in Twisted Bi‐ and Multilayer Graphene

Abstract: Graphene is a 2D honeycomb carbon crystal that exhibits unusual electronic structures and physical properties [1][2][3][4] that make it attractive for high-performance devices, such as transistors, [5][6][7][8] optical modulators, [9,10] and photodetectors. [9,11] Compared to single layer graphene, when two or more layers of graphene are stacked together with a twist angle, their electronic structure can be further enriched, giving rise to the van Hove singularity (vHS) with greatly enhanced carrier density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 41 publications
3
52
0
Order By: Relevance
“…[23][24][25] By electrostatically gating twBLG it is possible to alter these optical properties altogether as the electronic dispersion and correlation effects are modified, [26] which will profoundly affect the carrier dynamics and time-dependent response of the electronic structure to an optical excitation compared to standard Bernal-stacked bilayer graphene. [27] The energy-and momentum-dependent evolution of the interlayer hybridization between the Dirac cones of twisted graphene layers has been observed in angle-resolved photoemission spectroscopy (ARPES) experiments for large twists [28,29] and near the magic angle, [30,31] but the effect of gating in a functional device has not been previously explored. We achieve this…”
Section: Doi: 101002/adma202001656mentioning
confidence: 99%
“…[23][24][25] By electrostatically gating twBLG it is possible to alter these optical properties altogether as the electronic dispersion and correlation effects are modified, [26] which will profoundly affect the carrier dynamics and time-dependent response of the electronic structure to an optical excitation compared to standard Bernal-stacked bilayer graphene. [27] The energy-and momentum-dependent evolution of the interlayer hybridization between the Dirac cones of twisted graphene layers has been observed in angle-resolved photoemission spectroscopy (ARPES) experiments for large twists [28,29] and near the magic angle, [30,31] but the effect of gating in a functional device has not been previously explored. We achieve this…”
Section: Doi: 101002/adma202001656mentioning
confidence: 99%
“…In this review the preparation methods employed to produce 2D material are discussed briefly, and include Chemical Vapor Deposition (CVD) [ 7 ], Physical Vapor Deposition (PVD) [ 8 ], and mechanical exfoliation. The latter is the easiest way to prepare high-quality 2D materials in a laboratory; it can be applied to the most innovative materials because it is possible as soon as small bulk pieces of a material are produced.…”
Section: Introductionmentioning
confidence: 99%
“…This paper features some of the most interesting results obtained to date on graphene, transition metal dichalcogenides (TMDCs), and 2D heterostructures along with discussions about future instrument upgrades for spatially-, spin-, and time-resolved acquisitions. Graphene was a starting point for the investigation by spatially localized ARPES of 2D materials, an example of advanced spatially localized investigations on polycrystalline few layer graphene has been reported [ 7 ]. TMDCs have intriguing electronic, spintronic, and photonic properties, and the study of their band structure is of fundamental importance.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that there are three types of stacking, an AA one, which is simple hexagonal (it is not found in natural graphite and exists only in intercalated compounds such as C 6 Li and C 8 K, an AB stacking, hexagonal, known also as Bernal, and a rhombohedral ABC stacking. Additionally, a random stacking of these three types is called a turbostratic TS structure and often is obtained in laboratories.…”
Section: Stacking Ordermentioning
confidence: 99%
“…Recently, in bilayer graphene twisted at 1.1 degree superconductivity was found with critical temperature of 1.7K [5]. By manipulating doping levels these singularities are observed at angles up to 31 degrees [6]. It was shown that free-standing vdW heterostructure of graphene on hexagonal boron nitride (hBN), where a small lattice mismatch exists shows a buckled atomic structure formed as Moiré pattern [7].…”
mentioning
confidence: 99%